Public procurement of homogeneous goods: The Czech Republic case study - Jan Soudek; Jiří Skuhro (Charles University in Prague, Institute of Economic Studies (IES), 2013)
The goal of this paper is to show how institutional and procedural characteristics affect the final price of the public procurement. In order to get comparable prices, only public procurement of homogeneous goods is analyzed. Presented model attempts to explain the variation in unit price as a function of price estimated by the contracting authority, market price and characteristic of procurement procedure - type of procedure, number of bidders and use of electronic auction. We find that the final price in the electricity and natural gas public procurement is more sensitive to purchaser's estimate than to actual market price. At the same time, we identify that the final price is reduced by using open procedure, electronic auction or attracting more competitors.
Keywords: H57; D23; D73; C21; 330; public procurement; homogeneous goods; energy markets